The role of typical low vertical lattice sand barriers in regulating the airflow field on wind-eroded surfaces of photovoltaic power plants - Meng, Ruibing; Meng, Zhongju; Cai, Jiale; Li, Haonian; Ren, Yu; Guo, Lijun (Frontiers in Environmental Science, 2024)
Deserts are ideal places to build photovoltaic (PV) power plants, but this plants often face challenges from strong wind and sand activities during the operation and maintenance period, exploring the effects of PV power plant construction on wind disturbances and the control of wind and sand activities by different sand fixation measures is necessary. This study investigated the wind speed outside the PV plant, inside the plant without sand barriers measures (CK), and under three different sand-protecting barriers (gauze sand barriers (GZ), polylactic acid sand barriers (PLA), and grass grid sand barriers (GG)) inside the plant. Though calculated the surface roughness, friction velocity, wind protection effectiveness, and wind turbulence to determined the effectiveness of the barriers by these indexes comprehensively. The results show that: (1) The construction of desert PV power plant can effectively reduce the wind speed. Compared with CK, all three mechanical sand barriers within the plant reduced wind speed. Especially when the height less than 50cm, the GZ sand barriers reduced the wind speeds the most, with an average reduction rate of 101.5%. (2) All three sand barriers increased soil roughness and friction velocity within the power station. (3) At heights below 50cm, the GZ and GG sand barriers have better wind protection effectiveness than PLA sand barriers, while at hights above 100cm, the wind protection effect of PLA and GG sand barriers became less significant or even negligible (4) The wind disturbance caused by the three sand fixation measures increased with wind speed, the comprehensive performance of GZ and PLA sand barriers was superior than that of GG sand barriers and CK.